Optical Properties of the Urban Aerosol Particles Obtained from Ground Based Measurements and Satellite-Based Modelling Studies - Genrik Mordas; Nina Prokopciuk; Steigvilė Byčenkienė; Jelena Andriejauskienė; Vidmantas Ulevicius (Advances in Meteorology)
Applications of satellite remote sensing data combined with ground measurements and model simulation were applied to study aerosol optical properties as well as aerosol long-range transport under the impact of large scale circulation in the urban environment in Lithuania (Vilnius). Measurements included the light scattering coefficients at 3 wavelengths (450, 550, and 700 nm) measured with an integrating nephelometer and aerosol particle size distribution (0.5–12 μm) and number concentration (Dpa > 0.5 μm) registered by aerodynamic particle sizer. Particle number concentration and mean light scattering coefficient varied from relatively low values of 6.0 cm−3 and 12.8 Mm−1 associated with air masses passed over Atlantic Ocean to relatively high value of 119 cm−3 and 276 Mm−1 associated with South-Western air masses. Analysis shows such increase in the aerosol light scattering coefficient (276 Mm−1) during the 3rd of July 2012 was attributed to a major Sahara dust storm. Aerosol size distribution with pronounced coarse particles dominance was attributed to the presence of dust particles, while resuspended dust within the urban environment was not observed.